2014
DOI: 10.1007/s10646-014-1200-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PGPR Serratia marcescens BC-3 and AMF Glomus intraradices on phytoremediation of petroleum contaminated soil

Abstract: Soil contamination caused by petroleum hydrocarbons has become a worldwide environmental problem. Microorganism combined with phytoremediation appears to be more effective for removal and/or degradation of petroleum hydrocarbons from impacted soils. The current study investigated the effect of inoculated with PGPR Serratia marcescens BC-3 alone or in combination with AMF Glomus intraradices on the phytoremediation of petroleum-contaminated soil. Pot experiments were conducted to analyze the effect on plant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…(also identified in the present study) can significantely enhance the rate of petroleum hydrocarbons degradation (Alarc on et al, 2008;Yu et al, 2011;Dong et al, 2014;Xun et al, 2014). In the cases of fungi, Mirabal Alonso et al (2008) isolated two yeast species belonging to Rhodotorula and Cryptococcus (also identified in the present study) from the spores of Funneliformis mosseae (synonym Glomus mosseae) with a potential phosphate solubilization activity.…”
Section: Associations Between Amf Spores and Microbial Communitiessupporting
confidence: 59%
See 1 more Smart Citation
“…(also identified in the present study) can significantely enhance the rate of petroleum hydrocarbons degradation (Alarc on et al, 2008;Yu et al, 2011;Dong et al, 2014;Xun et al, 2014). In the cases of fungi, Mirabal Alonso et al (2008) isolated two yeast species belonging to Rhodotorula and Cryptococcus (also identified in the present study) from the spores of Funneliformis mosseae (synonym Glomus mosseae) with a potential phosphate solubilization activity.…”
Section: Associations Between Amf Spores and Microbial Communitiessupporting
confidence: 59%
“…Interestingly, some studies have demonstrated that the co‐inoculation of AMF with Proteobacteria such as Acinetobacter sp., Serratia sp., and Sphingomonas sp. (also identified in the present study) can significantely enhance the rate of petroleum hydrocarbons degradation (Alarcón et al ., ; Yu et al ., ; Dong et al ., ; Xun et al ., ). In the cases of fungi, Mirabal Alonso et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, S. marcescens has multiple roles after colonizing plants. Under environmental stimulation, it can change from a beneficial bacteria (promoting plant growth) to a plant pathogen [63,64]. Also, Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, prospective role in the remediation of environmental pollutants have been sightseen in recent times (Dong et al, 2014;Ajuzieogu et al, 2015;Hou et al, 2015). Organic compounds including PHs, pesticides, chlorinated compounds (polychlorinated biphenyl), explosives, organophosphate insecticides (diazinon and parathion), and surfactants (detergents) are more rapidly degraded by rhizospheric bacteria (PizarroTobías et al, 2015;Thijs and Vangronsveld, 2015).…”
Section: Rhizoremediation: Use Of Rhizobacteria To Enhance Hydrocarbomentioning
confidence: 99%